Handala e as fronteiras para descolorir: os cartuns de Naji al-Ali, insurgências poéticas e epistêmicas na luta de libertação popular Palestina - Silva Júnior, Israel Aparecido da (2022)
The present study focuses on the investigation of the imagery production and the artistic and political discourse contained in the cartoons of the character Handala, a Palestinian child bereft of bread and homeland but who is indignant and obstinate for the Palestinian popular liberation struggle.The character was introduced to the public through the refugee Naji al-Ali, following the unfolding of the Palestinian tragedy Al- Nakba.The first chapter provides a historical approach on how and why the British occupation of Palestine occurred, which promoted important changes that were already underway in that dynamic place of multiple social and cultural interactions. With administrative dominance of the Palestine Mandate, another foreign European political entity is projected onto Palestinian territory.Their goal: occupation, at the cost of native demographic hegemony. Different forms and technologies for violence have given rise to popular-based Palestinian struggles. Chapter two opens with an introduction to Palestinian art production under three theoretical approaches ( natives, exiles, and Israelis). Additionally we briefly go through the biography of the cartoonist known as Naji al-Ali to the production of his cartoons. In particular Handala, a refugee character who transits around urgent issues. Part of his works was collected and published as a book in Brazil, compiling some of the artworks that provided the images analyzed in this research. The methodology of this research aimed to identify through the study of images, the most relevant themes of the dispute between agents of imperial metropolises and Palestinian resistances through artists and the "theoreticians" who work along the margins and through the images.Starting from the assumption of colonial difference as a device that legitimized colonial occupation strategies in the historical Palestine and the scenarios of geopolitics, what were the responses given by the cartoonist and his works? Handala character was able to communicate both with the experiences of the native populations and with the diaspora communities as well.Part of the second and the third chapter analyze the imagery collection of cartoons produced between the decades 1970 and 1987.In these works, Handala and different thematic markers arise in the trenches of cartoon language: a border between journalism and the visual arts. It frames the perspective of everyday life and represents it from the Palestinians "relegated", impoverished and condemned of the land and the refugees from Palestine.The interdisciplinary field of Cultural Studies made it possible to establish approaches between native, insurgent, allied, and social movement theorists to the Palestinian discourse for popular liberation. Which role do images plays in Naji al-Ali's graphic discourse? What are the origins of Handala? What are the main themes found in the cartoons?It is a great challenge to translate to the Brazilian context so many images, concepts, and different repertoires and cultural landscapes with the broad objective of meaningfully reading images.From orientalism to decolonization of the view, we attempt to verify how the markers of coloniality and resistance relate to these visual products, evidencing internal and external disputes in the most distinct fields.On the Palestinian front, Handala appears on the gray borders between art, politics, life, and death.Motivated towards the end of apartheid and ethnic cleansing, this child character seeks to return home, without losing his memory and pride. It becomes a kind of portal between the past and today, demonstrating the never-ending struggle for dignity, self- determination and the right to return.By hiding her face, Handala invites us to look closely at the gray hues that art and life can meet.